The Responses of Selected Malaysian Trade Publishing Companies Towards Technological Development - Abdullah, Fadli; Mustafa, Siti Ezaleila (Jurnal Pengajian Media Malaysia, 2018)
In today’s digital age, content is no longer tied to a specific media format as it can come in any form, including in the digital format that can be distributed online. In the context of the content for book, since approximately 500 years ago, the printed book, which consists of the paper, print, binding, and glue, has been a prominent medium for content delivery. However, as digital technology advances, e-book has emerged along with printed book as an alternative to readers in the market. In some developed countries, the trend of e-book reading and buying have increased noticeably. However, looking at the broader context of the impact, e-book is only among the many aspects that have affected the industry. As argued by scholars, the end-product of the book industry is not the only aspect being affected, instead, the whole book creation process is experiencing changes. In order to have a better understanding of these issues, this study attempts to explore the current condition of Malaysian book publishing industry by analysing the responses of selected local trade publishing companies towards technological development in their pursuit of organizational success. In doing so, a case study of six local trade publishing companies comprises of large, small and medium, and government-funded publishers is conducted. From the case studies analysis, it is evident that these companies have responded vigorously to technological developments in their pursuit of organizational success. The finding shows that they are adopting the multi-platform strategy in almost every aspect of their business practices, especially in marketing and distributing of their content. In marketing, the use of Facebook, Instagram, Twitter, and YouTube have help them in promoting their books. Meanwhile, for the distribution of books, the emergence of online channels such as e-commerce, as well as mobile application, WhatsApp, have now opened up an opportunity for the publishers to enhance their sales. The Internet, computer technology, and social media are also becoming rather important in their book publishing practices.